An ethnography of urban collective gardens in Haute-Garonne: Contribution to the sociology of sensory experiences - Jules, Wilkens; Chateauraynaud, Francis; Dumat, Camille (Frontiers in Sustainable Food Systems, 2023)
Sensitive experiences made in the interaction between gardeners and their gardens have been studied in Occitania, as part of a research thesis in environmental sociology. Entering through situated experiences, we put into perspective a pragmatic reading making it possible to make visible in the gardens sensitive, ordinary, affective and emotional elements; which are discussed with the gardeners to clarify their beliefs, feelings, representations, values, and thus understand their intentions, knowledge, practices and techniques developed in the gardens. More broadly, our research explores how sensory experiences in the garden contribute to the reconfiguration of relationships with the environment on the one hand and with other humans on the other. The research hypothesis tested is as follows: “Through the grips they generate both in the body and the mind, through gestures, the mobilization of the senses, techniques, objects, sensitive experiences into garden strengthen the freedom and creativity of gardeners in their relationship with the environment.” An embedded ethnology in contact with experiences in the gardens is mobilized as a survey device to shed light on the sensitive aspects. The observations and exchanges with the gardeners immersed in the gardens, allow the integral restitution of in situ experiences in connection with things, beings, places and atmospheres.